Pengaruh Digital Competence Terhadap Work Productivity Karyawan Generasi Z di Kota Bima - Firdaus, Firdaus; Asyitah , Siti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine whether digital competence has a significant effect on the work productivity of Generation Z employees in Bima City. The type of research is associative research. The sampling technique uses purposive sampling, namely 100 respondents of Gen Z employees in Bima City. The research instrument used is a questionnaire using a Likert scale. The data analysis technique uses simple linear regression. The results of this study show that the value of t-count is 7.513 while the t-table is 1.660. These results indicate that the value (t count> t table), then Ha is accepted and Ho is rejected, meaning that digital competence has a significant effect on the work productivity of Generation Z employees in Bima City.